2015
DOI: 10.1097/sla.0000000000000747
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Nomograms for Prediction of Recurrence and Survival After Curative Liver Resection for Hepatocellular Carcinoma

Abstract: Our simple user-friendly calculators, which present graphically postsurgical prognostic models for recurrence and survival outcomes in patients with curatively resectable HCC, offer useful guidance to clinicians and patients for individually planning recurrence surveillance and adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
192
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(203 citation statements)
references
References 26 publications
9
192
1
1
Order By: Relevance
“…Pre-transplant serum tumor markers, namely alpha-fetoprotein (AFP) and protein induced by vitamin K absence or antagonist II, remain the most widely adopted surrogates for tumor biological aggressiveness used for that purpose78101316171819. However, microvascular invasion is consistently being reported as one of the most important tumor features, largely determining the long-term patient prognosis after both resection and transplantation202122232425. In a recent systematic review, the relative risk for worse 3-year disease-free survival associated with microvascular invasion was 3.4 for liver transplantation and 1.8 for liver resection26.…”
mentioning
confidence: 99%
“…Pre-transplant serum tumor markers, namely alpha-fetoprotein (AFP) and protein induced by vitamin K absence or antagonist II, remain the most widely adopted surrogates for tumor biological aggressiveness used for that purpose78101316171819. However, microvascular invasion is consistently being reported as one of the most important tumor features, largely determining the long-term patient prognosis after both resection and transplantation202122232425. In a recent systematic review, the relative risk for worse 3-year disease-free survival associated with microvascular invasion was 3.4 for liver transplantation and 1.8 for liver resection26.…”
mentioning
confidence: 99%
“…To evaluate the predictive accuracy of a nomogram, the C-index is widely used. The bootstrap-corrected C-index for the nomogram formulated in the present study was 0.77, which is comparable or higher than those of past studies, [33][34][35][36][37][38] suggesting the high accuracy of our nomogram for predicting 6-month survival rates. Therefore, in a heterogeneous group of patients with HCC who are referred for RT to LN metastasis, this nomogram can be used effectively to predict survival outcomes.…”
Section: Discussionmentioning
confidence: 42%
“…19,27,28,[32][33][34][35][36][37][38] However, in patients undergoing RT for LN metastasis, no prognostic grouping or nomogram has been suggested for use. In our study, a prognostic grouping by the number of risk factors was formulated based on the results of multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Shim et al reported on nomograms which showed good predictions for post-resectional recurrence and survival in patients with early stage HCC. 19 Based on the superiority of nomogram in prognostic prediction, we hypothesized that the model could also serve as an ideal tool to predict long-term post-resectional outcome in patients with huge HCC.…”
Section: Introductionmentioning
confidence: 99%